Harbor Island - Neggers, Carla (Neggers, Carla. Sharpe & Donovan novel, 2014)
While tracking down stolen artifacts from Boston to Ireland to the coast of Maine, Emma Sharpe, the granddaughter of a world-renowned art detective, and her fiancé, FBI deep-cover agent Colin Donovan, must outwit one of the smartest, most ruthless killers they have ever encountered.